Semiotic Analysis Of Adam Johnson's Short Stories In Fortune Smiles - Baddu, Radian Mahenra; Moelier, Dahlia D.; Batau, St. Haliah (Humaniora: Journal of Linguistics, Literature, and Education, 2025)
This research aimed to identify and analyse semiotic signs within Charles Sanders Peirce's triad (Icons, Indexes, and Symbols) in Adam Johnson's short story collection, Fortune Smiles. The objectives of the study were twofold: to describe the semiosis process of the signs and to classify them according to their subtypes. The study applied a descriptive-qualitative method with a semiotic approach, using Peirce's framework for data analysis and Arthur Asa Berger's classification to categorise symbols. The analysis revealed a total of 33 signs: 10 icon signs, 12 index signs, and 11 symbol signs. These signs were further classified into subtypes for a more detailed analysis. The 10 icon signs were divided into 7 topological, 1 diagrammatic, and 2 metaphorical icons. The 12 index signs included 8 symptoms, 3 tracks, and 1 designation index. The 11 symbol signs were categorised into 10 conventional and 1 universal symbol. Notably, no accidental symbols were identified, which aligned with their highly personal and character-specific nature. The use of Peirce's semiotic theory in this literary analysis provided more than just an explanation of the semiosis process where signs in a literary work were formed and acquired meaning. By further dividing these signs into subtypes, including the classification of symbols according to Arthur Asa Berger, the study offered a more in-depth explanation of sign types based on the relationship between the representamen and its object.